Islam Kontemporer: Antara Reformasi Dan Revolusi Peradaban - Ahmad Sulhan (Ulumuna, 2008)
The 19th and 20th centuries were periods for main transformation in Muslim history: periods of degradation and conquest, independence and revolution, renaissance and reform. Toward the 19th century, world power moved from Muslim world to Europe. It was remarked by emerging power of British, France, Spain, Russia, Netherlands, Italy and Portuguese. They dominated Muslim societies in Asia, Africa, and Middle East in economic, military, politic and ideological aspects. Muslim societies’ responses to Europe domination were diverse from rejection and confrontation to emigration and non-cooperative attitudes of traditional Muslim. They planned reform, reconstructed Islamic thinking and beliefs, reformed theology and Islamic law, and emphasized Muslim’s self-esteem significance, unity and solidarity in facing cultural threats and Europe colonialism. However, not few secular Muslims and reformers, were proud and greatly imitated Europe civilization and cultures. They did secularization that ended khalifah system in order to reconstruct Muslim societies.